Profile of Medication Error Incidents in the Dispensing Phase at the Pharmacy Installation of the Occupational Health Regional Public Hospital of West Java Province - Nur Hasanah, Firli; Emelia, Rida (Dinasti Health and Pharmacy Science, 2025)
Patient Safety Incidents are unintended events that pose a risk of harm to patients during the course of healthcare services. One common form is a medication error, which refers to mistakes in the medication process, particularly in the dispensing phase (errors in prepar tion and com-pounding of medications). This study aims to analyze medication errors occurring during the dispensing phase. The objective is to identify the causes and determine the percentage of medica-tion errors in the dispensing phase at the Pharmacy Department of RSUD Kesehatan Kerja, West Java Province. This study uses a descriptive analytical method with a retrospective approach. Data were collected using total sampling from all reported medication error incidents in the Pharmacy Department from July 2024 to June 2025. The results showed that the most frequent errors occurred in the category of wrong drug retrieval (72.30%), followed by labeling errors (20%), insufficient quantity dispensed (6.15%), and errors in handing over the medication to pa-tients (1.53%). No errors were found in the categories of administering drugs beyond instructions or dispensing expired or damaged medications. Preventive efforts may include implementing double checks, improving workflow systems and the physical environment, providing regular staff training, and utilizing appropriate technology.